2022
DOI: 10.3389/fpsyg.2022.929350
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on perinatal loss among Italian couples: A mixed-method study

Abstract: BackgroundPerinatal bereavement is an event that greatly impacts the emotional, psychological, and psychosocial aspects of those who want to have a child.ObjectivesSince there are few studies on the psychological impact of the COVID-19 pandemic on couples grieving for perinatal loss, this research aimed to survey this experience.ParticipantsBetween 2020 and 2021, in Italian provinces highly affected by the COVID-19 pandemic, 21 parents participated: 16 mothers (76%; mean age 36.2; SD: 3.1) and 5 fathers (24%; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The baseline findings indicated that COVID-19 restrictions have adversely impacted the experience of spontaneous pregnancy loss in couples [5], with follow-up results confirming the lasting detrimental effects on the processing of traumatic loss. These restrictions have strained relationships between healthcare providers and parents, limiting interactions with the family and friends network.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…The baseline findings indicated that COVID-19 restrictions have adversely impacted the experience of spontaneous pregnancy loss in couples [5], with follow-up results confirming the lasting detrimental effects on the processing of traumatic loss. These restrictions have strained relationships between healthcare providers and parents, limiting interactions with the family and friends network.…”
Section: Discussionmentioning
confidence: 84%
“…The number of participants, mothers and fathers, who filled out the questionnaire in the follow-up was 20 out of 45 of total participants at the baseline ( [5], see also Table 2). For 61.5% (50% of the mothers and 20% of the fathers) this was their first pregnancy, and 46% (37.5% of the mother and 60% of the fathers) had previous experience with miscarriage.…”
Section: Quantitative Resultsmentioning
confidence: 99%
See 3 more Smart Citations